A construção dos indicadores de desempenho como ferramenta de gestão estratégica na empresa contábil - França, Glaucius André (2011)
This research combines theoretical and methodological reflection on the creation of performance indicators that allow senior management accounting, keep track of whether the strategic objectives set for it, based on its Strategic Planning, will be achieved. For this, he needed the break up of the strategic objectives into specific objectives for groups, and for these, indicators were created to assist the managing partners of the company, whether or not they will achieve their goals, whether it would be necessary corrective measures to realign the accounting firm, so that it achieves its goals, based on its mission, vision, values and beliefs, fulfilling its role not only in front of their stakeholders in pursuit of business efficiency, but also to society . Therefore, the issue regarding the construction of performance indicators as a strategic management tool in the "accounting firm", responds favorably to issues of research, demonstrating that it is possible to construct models of indicators to monitor the performance of accounting firms, and in this sense, meet the specific objective, and to analyze the data information system that will allow the development of performance indicators, and identify what are the performance indicators that strategic planning needs to monitor what your goals are met. The methodology used was a case study in an accounting firm located in southern Brazil, in Londrina, Parana State